Autoimmune/Inflammatory Syndrome Induced by Adjuvants and Thyroid Autoimmunity - Watad, Abdulla; David, Paula; Brown, Stav; Shoenfeld, Yehuda (Frontiers in Endocrinology, 2017)
The autoimmune/inflammatory syndrome induced by adjuvants (ASIA), presented by Shoenfeld et al. in 2011 is an entity, which incorporates diverse autoimmune conditions induced by the exposure to various adjuvants. Adjuvants are agents which entail the capability to induce immune reactions. Adjuvants are found in many vaccines and used mainly to increase the response to vaccination in the general population. Silicone also has been reported to be able to induce diverse immune reactions. Clinical cases and series of heterogeneous autoimmune conditions including, systemic sclerosis, systemic lupus erythematosus, rheumatoid arthritis and others have been reported to be induced by several adjuvants. However, only a small number of cases of autoimmune thyroid disorder have been included under the umbrella of ASIA syndrome. Indeed, clinical cases of HT and/or subacute thyroiditis were observed after the exposure to vaccines as well as silicone implantation. In our review, we aimed to summarize the current knowledge on ASIA syndrome presented as endocrinopathies, focusing on autoimmune thyroid disorders associated with the various adjuvants.